Tolerance in famous texts (Journal of Parents and Teachers, 1995)
The importance of wisdom and universal love, urging to be perfect like the heavenly Father. Freedom is emphasized as a natural right to be granted to others and violence is rejected, promoting tolerance and mutual learning. The idea that prosperity is linked to goodness is criticized.
Keywords: wisdom; universal love; freedom; tolerance